Physiological and Transcriptional Responses to Acute and Chronic Thermal Stress in the Ark Shell Scapharca subcrenata - Zou, Desheng; Ning, Junhao; Lu, Xia; Wang, Xia; Chen, Min; Liu, Bo; Fang, Jun; Wang, Chunde (Frontiers in Marine Science, 2021)
Ark shells (Scapharca subcrenata) grown on the tidal flats are often exposed to high temperature stresses in summer. In order to better understand their adaption to extreme or natural high temperature, we first determined the 96-h upper lethal temperature of ark shell and then investigated their physiological and transcriptional responses to acute or chronic thermal stress at the 96-h upper median lethal temperature (32°C). A significantly higher cumulative mortality (52% in 96 h) was observed in the acute heating treatment (AHT) group than that (22% in 7 days) in the chronic heating treatment (CHT) group. The apoptosis and necrosis rates of hemocytes were increased significantly in a time-dependent manner under both thermal stress strategies. Activities of antioxidant enzymes [superoxide dismutase (SOD) and catalase (CAT)] increased dramatically in a short time followed by a quick decline and reached to a lower level within 12 h in the AHT group, but maintain relatively high levels over a long period in the CHT group. The contents of malondialdehyde (MDA) were increased significantly firstly and restored to the original later in both acute and chronic thermal stress. Moreover, expression of the genes related to heat shock proteins (HSPs; HSP90, HSP70, HSP20, and sHSP), apoptosis [TNF receptor-associated factor 6 (TRAF6), glucose regulated protein 78 kD (GRP78), and caspase-3 (Casp-3)] and antioxidant responses [glutathione S-transferase (GST) and multidrug resistance protein (MRP)] could be induced and up-regulated significantly by thermal stress, however, expression of regucalcin (RGN), metallothionein (MT), and peroxiredoxin (PRX) was down-regulated dramatically under the two heating treatments. These results suggested that anti-apoptotic system, antioxidant defense system and HSPs could play important roles in thermal tolerance of ark shells, and the heat-resistant ark shell strains could be selected continuously by properly chronic thermal stress.